2016
DOI: 10.1111/acem.12941
|View full text |Cite
|
Sign up to set email alerts
|

False‐negative Interpretations of Cranial Computed Tomography in Aneurysmal Subarachnoid Hemorrhage

Abstract: Objectives: Prior studies examining the sensitivity of cranial computed tomography (CT) for the detection of subarachnoid hemorrhage (SAH) have used the final radiology report as the reference standard. However, optimal sensitivity may have been underestimated due to misinterpretation of reportedly normal cranial CTs. This study aims to estimate the incidence of missed CT evidence of SAH among a cohort of patients with aneurysmal SAH (aSAH).Methods: We performed a retrospective chart review of emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Our study revealed that 4.0% of patients diagnosed with SAH at ED had a normal non-contrast head CT. This result is slightly lower than previously published findings showing percentage of CT-negative SAH between 4-20% [9][10][11]. The discrepancies may be partially explained with differences in parameters of CT scanner and in experience of radiologists describing the images.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Our study revealed that 4.0% of patients diagnosed with SAH at ED had a normal non-contrast head CT. This result is slightly lower than previously published findings showing percentage of CT-negative SAH between 4-20% [9][10][11]. The discrepancies may be partially explained with differences in parameters of CT scanner and in experience of radiologists describing the images.…”
Section: Discussioncontrasting
confidence: 76%
“…Optimizing the quality of diagnostics and care of patients with suspected SAH is an important issue in recent Emergency Nedicine and Neurology literature. One of the solutions for prolonged diagnostics of headache in ED is extending imaging after originally negative non-contrast head CT scan to include CT-angiography if SAH remains part of the differential diagnosis, which may significantly reduce the risk of overlooking aneurysmal SAH [11]. Another approach is to focus on assessment of initially performed non-contrast head CT scan, as radiological evidence of SAH is frequently unrecognized [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal fluid analysis is a crucial method in the diagnostic process if a subarachnoid hemorrhage (SAH) is clinically suspected but findings from cerebral imaging are negative or inconclusive. This is especially important in cases with an increased time interval between the suspicious clinical event and the cerebral imaging as the sensitivity of cerebral imaging declines significantly over time [ 1 , 2 ]. When faced with prolonged time intervals between a suspicious event with acute severe headache and clinical examination, CSF analysis may be the only diagnostic tool to verify a SAH [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even in such cases, it might not be possible to clearly observe hematoma. Patients with small hemorrhages, who are the most likely to receive an incorrect clinical diagnosis, are also more likely to have negative results or misinterpretation on CT [ 17 , 18 ]. Although magnetic resonance technology is continually advancing and can detect aneurysms, standard magnetic resonance imaging (MRI) is inferior to CT in terms of detecting acute SAH [ 19 ].…”
Section: Discussionmentioning
confidence: 99%